2015
DOI: 10.1007/s00277-015-2441-9
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplastic syndromes in Chernobyl clean-up workers

Abstract: The studies of the recent decades posed the question of the association between radiation exposure and myelodysplastic syndromes (MDS). This association has been proved in secondary MDS originating upon exposure to chemotherapeutics and/or radiation therapy. The long-term study in Japanese atomic (A)-bomb survivors demonstrated the significant linear dose-response for MDS confirming the link between radiation exposure and this form of hematopoietic malignancies. All these findings provide the strong basis for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Few studies have investigated the clinical characteristics of primary MDS after accidental radiation exposure. Recently, Gluzman et al . reported data on MDS among clean‐up workers who were exposed to radiation at the Chernobyl nuclear power plant accident during 1986–1987 (exposure dose range, 0.075–0.25 Gy).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have investigated the clinical characteristics of primary MDS after accidental radiation exposure. Recently, Gluzman et al . reported data on MDS among clean‐up workers who were exposed to radiation at the Chernobyl nuclear power plant accident during 1986–1987 (exposure dose range, 0.075–0.25 Gy).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated the clinical characteristics of primary MDS after accidental radiation exposure. Recently, Gluzman et al (17) reported data on MDS among clean-up workers who were exposed to radiation at the Chernobyl nuclear power plant accident during 1986-1987 (exposure dose range, 0.075-0.25 Gy). They diagnosed 23 MDS and five CMML cases based on the WHO classification during 1996-2012, but did not assess the effect of exposure dose on the clinical course.…”
Section: Discussionmentioning
confidence: 99%
“…A clear dose-effect relationship, evident and linear with the dose for irradiation such as nuclear blasts (Gluzman et al 2015), is not apparent in radionuclide therapies such as PRRT. In the latter, the doses delivered to the bone marrow are generally low (mean 0.02-0.07 Gy/GBq), resulting in a mean dose, for typical administrations of 7.4 GBq, of 0.15-0.5 Gy.…”
Section: :8mentioning
confidence: 99%
“…A critical parameter is the different sensitivities of DNA to radiation during the cell cycle and intrinsic host repair mechanisms (Bourguignon et al 2005). High-dose total body irradiation, as in atomic bomb survivors, Chernobyl nuclear disaster liquidators, or large-field conditioning radiotherapy before bone marrow transplantation, is known to be leukemogenic in a dose-dependent manner (Gluzman et al 2015). However, the absolute rate of MDS is very low.…”
Section: Main Textmentioning
confidence: 99%